1996
DOI: 10.1002/(sici)1099-1646(199603)12:2/3<131::aid-rrr385>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Habitat of Plants in Streams

Abstract: Plant development in unshaded streams is reviewed within the context of a conceptual habitat model. Resource factors (incorporating light, nutrients and temperature) predominantly govern the processes of biomass gain and hydraulic factors (incorporating separate temporal and spatial scales) predominantly govern the processes of biomass loss. It is postulated that differences in hydraulic stability among streams over periods greater than a year govern whether a stream (or site) is dominated by periphyton, bryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 62 publications
4
86
0
7
Order By: Relevance
“…In our experiments, the growth dynamics of periphyton and the change in its diversity over time matched those reported in numerous other studies (Biggs 1996;Guasch et al 1997;Hillebrand and Sommer 2000;Sekar et al 2002): the number of algal species, revealed by finger printing, indicated a loss of richness and diversity. We observed a decrease in the Shannon index, in the number of bands present per profile, and a change in species composition between the two stages of maturity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our experiments, the growth dynamics of periphyton and the change in its diversity over time matched those reported in numerous other studies (Biggs 1996;Guasch et al 1997;Hillebrand and Sommer 2000;Sekar et al 2002): the number of algal species, revealed by finger printing, indicated a loss of richness and diversity. We observed a decrease in the Shannon index, in the number of bands present per profile, and a change in species composition between the two stages of maturity.…”
Section: Discussionsupporting
confidence: 91%
“…In our experiments, the biomass, number of algal and bacterial cells, and primary production increased under all experimental conditions. Schematically, global changes in periphyton display three successive phases (Biggs 1996): a colonization phase, an exponential growth phase and an aging phase. The start of the growth phase is characterized by a low biomass and fairly high diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, subsidy (or stress) will influence abundance more than the species pool because the subsidy can only act on the available pool, but will directly contribute to recruitment success. Hydraulic disturbance is also more likely to influence abundance more than species pool because, although different taxa may be more susceptible to losses associated with hydraulic stress (Biggs 1996), it is unlikely that species would be totally lost from a wetland (Riis and Biggs 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low current velocities in these lakes allow small particles to settle and these may then serve as substrates for the colonization of aquatic plants. Aquatic vegetation is principally limited by high current velocity and low light conditions (Barko et al, 1986;Biggs, 1996). Shallow fluvial lakes thus represent ideal environments for macrophyte development.…”
Section: Introductionmentioning
confidence: 99%